FORMATION OF PROFESSIONAL COMPETENCE OF FUTURE ENGINEERS ON THE BASIS OF INTERDISCIPLINARY INTEGRATED EDUCATION OF PHYSICS (American Journal of Technology and Applied Sciences, 2023)
In the article, the professional competence of engineering students in physics based on interdisciplinary integrated education the method of formation is explained.